Direct etching at the nanoscale through nanoparticle-directed capillary condensation. Issue 16 (20th April 2020) - Garín, M.; Khoury, R.; Martín, I.; Johnson, E. V.
Abstract : A chemical is delivered with nanoscale precision through vapor phase transport and capillary condensation at points defined by nanoparticles. Abstract : We report a method to locally deliver a chemical etchant at the nanoscale in the vapor phase by capillary condensation forming a meniscus at the nanoparticle/substrate interface. The process is simple, scalable and does not require functionalization of the nanoparticles. Furthermore, it does not rely on any specific chemical properties of the materials other than the solution being aqueous and the wettability properties of the surfaces involved, which should enable its application to other material and chemical combinations. In particular, in this work we demonstrate the proposed process by periodically pattering a SiO2 layer using a self-assembled monolayer of polystyrene particles exposed to HF vapors. The patterned SiO2 layer is then used as a mask to etch a pattern of inverted nanopyramids on Si. The silicon nanopatterning has been demonstrated for particles sizes ranging from 800 nm down to 100 nm, providing pyramids with a size down to 50 nm for 100 nm nanoparticles.